EFEKTIVITAS PELAYANAN APLIKASI E-COURT DI PENGADILAN NEGERI PEKANBARU - Simto R. Simanjorang; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Effectiveness can be said as the result or output of a process that is pursued through the goals to be achieved, strategies, policies, careful planning, program preparation and of course requires infrastructure and continuous monitoring.The purpose of this study is to see whether this application has been effective in serving the Pekanbaru District Court, and also to find out what the inhibiting factors are. The type of research used in this research is qualitative with a descriptive approach. Qualitative research using a descriptive approach and the data required are primary data and secondary data derived from observations, interviews and documentation analyzed by researchers so as to obtain accurate and clear data regarding the effectiveness of e-court application services at the Pekanbaru District Court. The results of this study indicate that the effectiveness of the e-court application service at the Pekanbaru District Court in accordance with the regulations contained in Perma No. 1 of 2019 concerning case administration and court trials electronically has been going quite well.In terms of objectives, strategies, programs and facilities and infrastructure it can be said to be good so that these things make this application can be used in services in the District Court for people who need services in the judiciary. However, there are still inhibiting factors such as network-related problems that often disrupt the service in this application. Apart from that, there is still a lack of information and socialization to the public regarding this application, so that people still do not know about this application. Keywords:Service Effectiveness, Electronic Administration, E-Court